First Extensive Analysis of 18F-Labeled Fluorodeoxyglucose Positron Emission Tomography–Computed Tomography in a Large Cohort of Patients With HIV-Associated Hodgkin Lymphoma: Baseline Total Metabolic Tumor Volume Affects Prognosis. Issue 12 (20th April 2022) - Louarn, Nicolas; Galicier, Lionel; Bertinchamp, Rémi; Lussato, David; Montravers, Françoise; Oksenhendler, Éric; Merlet, Pascal; Gérard, Laurence; Vercellino, Laetitia
Abstract : PURPOSE: 18 F-labeled fluorodeoxyglucose positron emission tomography with computed tomography ( 18 F-FDG PET-CT) data in HIV-associated Hodgkin lymphoma (HIV-HL) are scarcely reported. In addition to the description of the characteristics of both baseline and interim 18 F-FDG PET-CT examinations (PET1 and iPET, respectively), the aim of this study was to assess the prognostic value of PET1 and previously identified clinical parameters in this population. PATIENTS AND METHODS: PET1 of 109 patients with HIV-HL, treated with doxorubicin, bleomycin, vinblastine, and dacarbazine chemotherapy regimen since 2007, and 104 iPET were centrally reviewed. All the patients were enrolled in an ongoing prospective single-center cohort of HIV-associated lymphoma. RESULTS: Most patients had a disseminated disease according to the Ann Arbor classification (30% stage III and 43% stage IV), with especially bone marrow and liver as extranodal localizations. After a median follow-up of 6.7 years, 12 patients relapsed (11%) and 13 died (12%). Five-year progression-free survival (PFS) was 75.1%, and 5-year overall survival was 86.1%. Median total metabolic tumor volume (TMTV) was 121.4 cm 3 . The optimal TMTV cutoff identified for prognostic analysis was 527 cm 3, with a 2-year PFS of 71% in the 20 patients with TMTV > 527 cm 3, compared with 91% in the 89 patients with TMTV ≤ 527 cm 3 ( P = .004). On multivariate analysis, a high TMTV was the only parameter independently associated with PFS. CONCLUSION: In this large series of HIV-HL patients with a homogeneous management, high TMTV on PET1 examination was associated with a poor prognosis.